Мальчишки с улицы Пала: повесть / Ференц Молнар - Молнар Ференц (ВАГРИУС, 2007)
Экземпляры: ф.8 (2008) / Инвентарный номер: 51938 / Цена: / Сис.шифр: 84(4Вен)6-4 / Авт.знак: М 75 / ГРНТИ: 17.82.93 / ББК: 84(4Вен)6-44